Kenaikan Harga Menjelang Lebaran Berdasarkan Teori Penawaran Islam - Nurul A'yun; kotimah (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2024)
Price is one of the elements in buying and selling transactions, namely the existence of a clear price for the object being bought and sold. The increase in prices of goods and services ahead of Eid is often a concern for the public. This incident often has negative consequences, especially for consumers who feel burdened by the increase in living costs from the origin of main ingredients to other products. Meanwhile, the Islamic concept is very detailed in how to regulate one's way of life so as not to be burdened by any conditions. Price is one of the elements in buying and selling transactions, namely the existence of a clear price for the object being traded. Therefore, the price of a product is one of the determinants of the size of market demand. Thus, price is always a measure of whether someone will make a purchase or not to fulfill their life needs. Where currently the price of basic necessities has soared (increased) because basic necessities always experience price fluctuations. This research uses qualitative research methods and Library Research data collection techniques as well as descriptive methods. The source of document data that can be obtained from the field is in the form of books, archives, magazines, and documents related to the research focus. As a result of research, it can be seen that prices leading up to Eid are very important in Islam